A Case of Neuromyelitis Optica: Puerto Rican Woman with an Increased Time Lag to Diagnosis and a High Response to Eculizumab Therapy. (18th February 2022) - Vega, Ramón; González, Benjamín; Ortiz, Kiara; Martínez, Viviana; Carmona, David; Vicente, Ivonne; Chapa, Javier; Chinea, Ángel
Abstract : A link between intractable hiccups, as the initial symptom, and a possible neuromyelitis optica spectrum disorder (NMOSD) diagnosis is confusing but vital and may not be made by health care providers (HCPs) if they are not aware of the 2015 NMOSD criteria. Early diagnosis and adequate treatment are essential to prevent disease progression. We report the case of a 46-year-old Puerto Rican female who presented intractable hiccups when she was 31 (in 2004). Almost 15 years passed since the initial symptom, and after two severe relapses, she received a formal NMOSD diagnosis in March 2019. Treatment started with rituximab 1000 mg IV in April 2019. However, a lack of response to treatment led to a switch to eculizumab therapy in August 2019. The patient had cervical and brain magnetic resonance imaging (MRI) conducted in June 2020, which depicted a remarkable decrease in swelling and hyperintensity within the cervical spinal cord with no enhancing lesions when compared with the first MRI from February 2019. In addition, the patient suffered no new relapses, an improvement regarding disability, and a reduction of the cervical spinal cord lesion size. Nonetheless, this substantial decrease does not occur on all NMOSD patients, but more awareness of the disease is needed, especially in Puerto Rico. This case illustrates the efficacy of eculizumab therapy and the importance of differentiating the clinical, histopathological, and neuroimaging characteristics that separate demyelinating autoimmune inflammatory disorders, such as NMOSD and multiple sclerosis (MS).